Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 38/IX Jambi Kecil dengan Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Tahun Ajaran 2018/2019 - Yusmanita Yusmanita (Universitas Batanghari Jambi, 2022)
This study aims to examine how to improve the mathematics learning outcomes of fourth grade students of SD Negeri 38/IX Jambi Kecil by using the two stay two stray (TSTS) type of cooperative learning model for the 2018/2019 academic year. This research uses Classroom Action Research (CAR). Respondents of this study were fourth grade students of SD Negeri 38/IX Jambi Kecil which consisted of 28 people. The results showed that the cooperative learning model type two stay two stray (TSTS) can improve the learning outcomes of fourth grade students at SD Negeri 38/IX Jambi Kecil. The increase can be seen from the average score of students on the pre-cycle test, namely (53.13) which is still in the